Metastatic Cutaneous Squamous Cell Carcinoma: The Importance of T2 Stratification and Hematologic Malignancy in Prognostication. Issue 8 (August 2016) - Stevenson, Mary L.; Kim, Randie; Meehan, Shane A.; Pavlick, Anna C.; Carucci, John A.
Abstract : BACKGROUND: While infrequent, nodal metastases in cutaneous squamous cell carcinoma (cSCC) can result in death from disease. Identification of those at risk for metastases is key to improved prognostication and treatment. OBJECTIVE: To review metastatic cSCC at the study institution. METHODS AND MATERIALS: Sixteen patients with metastatic cSCC were identified at the New York University Dermatologic Associates and Cancer Associates from 1998 to 2013. Patients were staged with American Joint Committee on Cancer (AJCC) and modified Brigham and Women's Hospital (BWH) criteria and compared to 32 control subjects. RESULTS: Seven of 16 patients were identified as Stage T2 by AJCC criteria and Stage T2b by BWH criteria; two patients were on Stage T1, three patients were on more advanced T stages, and four patients lacked primary tumor data. Five patients had hematologic malignancy, and one patient had a solid-organ transplant. CONCLUSION: The modified BWH criteria aims to better prognosticate the large group of T2 AJCC tumors, resulting in the majority of mortality. In the experience of the authors, the majority of patients with metastatic disease were on T2, stratifying to stage T2b by BWH criteria, or more advanced T stages. The findings of this study support BWH stratification of T2 tumors and also indicate that hematologic malignancy is a significant comorbidity associated with a poor outcome.